Capacity Development of Human Resource in Local Government to Improve Public Service Quality - Said, Moh. (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
Capacity development of human resource in relation to the government apparatus’ professionalism is an important aspect to consider when it comes to human resource development within the government. This is because it has a close relationship with their function as public servants. The higher the apparatus’ capacity is, the better they serve the public. However, the fact remains that the apparatus’ capacity has not yet met the required standard. This is mainly influenced by the apparatus’ low working ethos and their negative perspectives and attitudes that, in turn, prevent them from working effectively. To overcome this problem, it is suggested that the government restructures the institution through promoting a change in the working culture and behavior, reforming the institution’s departments based on the actual needs, endorsing efficiency, improving the public service to improve society at large, and increasing the apparatus’ professionalism.